Students Responses to New Learning Environmental Using Canva Application at the Newton Law’s - Kenya Luthfia Nur Shabrina; Muhammad Syaipul Hayat; Eko Retno Mulyaningrum; Endang Sularni (Jurnal Pembelajaran Fisika, 2023)
The purpose of this study is to find out students' responses to the New Learning Environmental program using the Canva application on Newton's law material. Based on the results of observations and interviews conducted in SMP Negeri 37 Semarang, it assumes a new learning environment or learning innovation to improve students' skills and students' understanding of Newton's law material. This study used a descriptive qualitative method in conducting observations and interviews. Class VII C was used as a sample. The results of the new learning environment were several answers in the training lessons on using the Canva application, which was helpful in the tasks in the form of products about Newton's law (infographics, mind mapping, posters, and videos) of material. During the learning, the students are very enthusiastic, free to be creative, and even free to change seats while learning. Based on this, it can be concluded that the New Learning Environment supported by the Canva application of Newton's law material received a positive responses from the students during the learning process.Keywords: Students Responses, New Learning Environmental, Canva Application, Newton Law’sDOI: http://dx.doi.org/10.23960/jpf.v11.n1.202302